One-stage Surgical Management for Lumbar Brucella Spondylitis by Posterior Debridement, Autogenous Bone Graft and Instrumentation: A Case Series of 24 Patients. Issue 19 (1st October 2017) - Chen, Yangbin; Yang, Jun-Song; Li, Tao; Liu, Peng; Liu, Tuan-Jiang; He, Li-Min; Qian, Li-Xiong; Hao, Ding-Jun
Abstract : Study Design: Clinical case series. Objective: The aim of this study was to explore the efficacy and safety of one-stage debridement, autogenous bone graft, and instrumentation for lumbar brucella spondylitis (LBS) via a posterior approach. Summary of Background Data: Reports on LBS are sporadic, and the therapeutic effect and safety of surgical interventions have not been assessed in clinical studies. Methods: Between January 2012 and January 2014, 24 consecutive patients with symptomatic LBS who underwent a one-stage operation that combined debridement, autogenous bone graft, and instrumentation via a posterior approach were enrolled. Back pain was measured using the visual analog scale (VAS). The neurological status was evaluated with the American Spinal Injury Association (ASIA) scale. Bone healing was evaluated based on postoperative plain x-ray or computed tomography. Results: All cases were followed up for an average of 14.3 + 3.5 months. The VAS scores were significantly improved at every follow-up interval. An improvement of at least one grade level was observed in the ASIA score of each patient. The average time of bone fusion was 6.8 + 1.6 months. Significant improvements of the average segmental Cobb angle was observed from a preoperative value of 18.4° + 4.6° to a last follow-up value of 21.1° ± 3.7°. At the last follow up, the titers of antibodies against the standard tube agglutination test, erythrocyte sedimentation rate, and C-reactive protein were negative for all patients. Conclusion: For LBS, systemic antibrucellosis chemotherapy is the cornerstone of treatment. When cauda equine syndrome, radiculopathy, spinal instability, and severe back pain caused by extradural nonabsorbable abscess or progressive collapse are present, surgical intervention is inevitable. One-stage debridement, autogenous bone graft, and instrumentation via a posterior approach could represent an alternative treatment for LBS, and the efficacy and safety of these techniques are satisfactory. Level of Evidence: 4